Darknet – selected criminological, forensic and legal aspects of encrypted computer networks - Wojciechowski, Hubert (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
The article raises issues concerning encrypted networks, their content and security. The following terms are explained: Darknet, Deep Web and Dark Web. The article presents some technical aspects of The Onion Router software and its origins. It also includes some characteristic features of the usage of such a tool and of the community which has developed around it. A legal and forensic assessment of the activity placed in the Darknet is presented. The author believes that the phenomenon of TOR software should not be evaluated negatively and the author predicts its rapid development.